FORMULASI SEDIAAN SERBUK EFERVESEN DARI EKSTRAK ETANOL ANGKAK (MONASCUS PURPUREUS) DENGAN METODE FOAM-MAT DRYING - Mubarok, Fajar (P3M STIKes Bakti Tunas Husada, 2020)
Indonesia has various types of plants that have potential as medicine to overcome health problems in line with the expansion of the traditional medicine industry. One example of plants from the Zingiberaceae family is Hedychium coronarium, which is not widely known by the community despite it has efficacy as an antibacterial which is not inferior to other Zingiberaceae family. The research was conducted to determine whether the Hedychium coronarium rhizome shown to have antibacterial activity against the growth of Staphylococcus aureus and Escherichia coli, knowing antibacterial compound that contained in Hedychium coronarium rhizome, also knowing the most effective extraction method to take the antibacterial compound from Hedychium coronarium rhizome. The gandasuli rhizome was extracted by maceration and reflux with 96% ethanol. Antibacterial activity test carried out by the agar diffusion method, and the analysis of antibacterial compounds with bioautography, and the results are monitored with vanillin-sulfuric acid. Maceration and reflux extract at a concentration of 90% have antibacterial activity with inhibition zones, each for 8 and 10 mm against Escherichia coli as well as 9 and 10 mm against Staphylococcus aureus. Bioautography results show a positive effect on the appearance of vanillinsulfuric acid. Reflux extract has better antibacterial activity, while the antibacterial compound is an essential oil group.